PENINGKATAN KEBERHASILAN PENGIRIMAN DATA PADA LINGKUNGAN VANET - Perkasa, Johan Ericka Wahyu; Prasetyo, Koko Wahyu (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2017)
VANET is a fairly new technology that enabling data to sent through vehicles wirelessly. The most challenging part is because VANET using ad-hoc principle, so there will no direct connection between sender and receiver. Data will be transmitted to nearby vehicles wirelessly. Routing algorithm take the most important part to find the best path from sender to receiver. This research will investigate Static Intersection Node effect to increase packet delivery ratio in VANET.Keywords: VANET, Static Intersection Node, Packet Delivery Ratio